Avaliação de camadas de carbonetos e boretos produzidas em aço AISI 4340 por meio de tratamentos termorreativos - Ferreira, Suellen Terroso de Mendonça (2019)
Very hard and wear resistant layers, consisting of Fe-B and NbC, were produced in AISI 4340 steel, by means of thermoreactive treatment in a molten borax bath with addition of B4C and Fe-Nb. The samples were characterized by optical and electron microscopy, X-ray diffraction, nanoindentation, Vickers microhardness, adhesion test and reciprocating wear. In the case of a bath containing only B4C, layers of borides were produced, composed of the FeB and Fe2B phases, with a mean thickness of 192 µm and a surface hardness of approximately 2000 HV. For the bath containing Fe-Nb / B4C was obtained layer of NbC with average thickness of 7.7 µm and hardness of approximately 3000 HV. The adhesion test showed excellent adhesion of the NbC layer to the substrate. The wear resistance of the layers was evaluated through the reciprocating wear test, and the sample with NbC layer showed remarkably the best performance with extremely low wear.